The Role of AI-Driven Marketing Insights in Enhancing Financial Performance and Competitive Advantage - Julaeha, Lia Siti; Ramdhan, Dadan; Winanto, Sujoko (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the role of AI-driven marketing insights in enhancing financial performance and competitive advantage from an interdisciplinary business perspective. As organizations increasingly operate in data-intensive environments, artificial intelligence has emerged as a strategic tool capable of transforming marketing data into actionable insights that support managerial and financial decision-making. Using a qualitative research design with a library research approach, this study synthesizes conceptual and empirical literature from marketing, finance, and strategic management to examine how AI-driven marketing insights contribute to firm performance. The analysis reveals that AI-driven marketing insights play a critical role in improving decision quality, marketing efficiency, and financial accountability by linking marketing activities directly to measurable financial outcomes such as revenue growth, cost optimization, and return on investment. Furthermore, the integration of AI capabilities into marketing analytics strengthens firms’ ability to develop sustainable competitive advantage through superior customer understanding, faster market responsiveness, and enhanced strategic alignment between marketing and finance functions. The findings also highlight the importance of organizational integration and data-driven culture in maximizing the financial value of AI adoption. This study contributes to the literature by offering a holistic conceptual framework that positions AI-driven marketing insights as a strategic capability rather than a purely technological tool. The research provides valuable implications for academics and practitioners seeking to understand how artificial intelligence can be leveraged to align marketing strategies with financial performance and long-term competitiveness.